Animal Satire
XII, 431 p.
Keywords: Animal Satire presents a cultural history of animal satire, a critically neglected but persistent presence in the history of cultural production, in which animals expose human folly while the strategies of satire expose the folly of human-animal relations. Highlighting the teeming animal presences across the history of satirical expression from Aristophanes to Twitter, with chapters on key works of literature, drama, film, and a plethora of satirical media, Animal Satire reveals the rich rhetorical significance of animality in powering the politics of satire from ancient and medieval through modern and contemporary times. More pressingly, the book makes the case for the significance of satire for understanding the real-world implications of rhetoric about animals in ongoing struggles for justice. By gathering both critical and creative examples from representative media forms, historical periods, and continents, this volume aims to enrich scholarship on thehistory of satire as well as empower creative practitioners with ideas about its practical applications today. Robert McKay is Professor of Contemporary Literature, School of English, University of Sheffield, UK. He has co-edited Animal Remains (2022), Against Value in the Arts and Education (2016), and Werewolves, Wolves and the Gothic (2017). He is the co-author (with the Animal Studies Group) of Killing Animals (2006). Susan McHugh is Professor of English, School of Arts and Humanities, University of New England, USA. She is the author of Love in a Time of Slaughters: Human-animal Stories against Extinction and Genocide (2019), Animal Stories: Narrating across Species Lines (2011), and Dog (2004). She is co-editor of several volumes, including Posthumanism in Art and Science (2021) and Indigenous Creatures, Native Knowledges, and the Arts: Animal Studies in Modern Worlds (Palgrave 2017). Robert McKay and Susan McHugh are co-editors (with John Miller) of the Palgrave Studies in Animals and Literature book series, as well as the volume The Palgrave Handbook of Animals and Literature (Palgrave 2021).